Peningkatan Perencanaan Karir Melalui Layanan Bimbingan Kelompok di SMA Kelas X Swakarya Salapian - Purbatua Manurung; Nuri Maulida; Syafika Ripani Siregar; Lilis Syahriani; Muhriana Pohan; Rajus Sya’abi Abdillah (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity was motivated by the low career planning skills of grade X students of SMA Swakarya Salapian, characterized by confusion in determining career choices and fear of discrepancies between plans and future expectations. The purpose of this activity is to improve students' understanding and skills in career planning through group guidance services. The service methods used include community education through socialization and counseling as well as mentoring through group discussions. The activities were carried out through preparation, implementation, and evaluation stages. The results of the activity showed that group guidance services were able to help students identify their interests, talents, and potential and increase students' courage in expressing career problems they faced. Evaluation through observation and questionnaires showed an increase in students' understanding of the importance of career planning. Thus, group guidance services effectively provide education and practical skills for students in planning their future careers more maturely and realistically.